On the Homotopy Asymptotic Method of Quantum Zakharov-Kuznetsov Equation in Ion Acoustic Waves - ABDOU, Mohamed Aly; ELGARAYHI, Ahamed (Walailak Journal of Science and Technology (WJST), 2015)
Here, we investigate the effectiveness of the optimal homotopy asymptotic method (OHAM) with a symbolic computational method for constructing the approximate solution for quantum Zakharov- Kuznetsov equation that is derived to describe the in magnetized plasma in ion acoustic waves. The results reveal that the method is explicit, effective and easy to use. The proposed method is a strong and easy to use analytic tool for nonlinear problems and does not need small parameters in the equations. The results obtained here reveal that the proposed method is very effective and simple for solving nonlinear problems. The basic ideas of this approach can be widely employed to solve other strongly nonlinear evaluation form equations arising in physics.